Development of a recipe for a «Solodok» multicomponent mixture to improve the quality of pastries - Bilyk, Olena; Burchenko, Liudmila; Kochubei-Lytvynenko, Oksana; Bondarenko, Yuliia (My University, 2021)
The object of research in this work is a baked product enriched with a mixture of sprouted grains, ground cinnamon, apple pectin, dry wheat gluten, ascorbic acid. Pastries occupy an important place in the production and sale of food products and have a high calorie content. To reduce the energy value of pastry products, it is proposed to replace wheat flour in the recipe with a mixture of germinated grains of wheat, oats, barley and corn. In this work, the properties of such mixtures were studied using the example of a mixture of the «CHOICE» company (Ukraine). The mixture of germinated grains of cereals of wheat, oats, barley and corn of this company is rich in dietary fiber, nonessential and irreplaceable amino acids, microelements and macroelements, vitamins. It has been established that a rational substitution of premium wheat flour for a mixture of germinated grains in the recipe for pastry products is 50 %. Due to the germination process, a large amount of amylolytic and proteolytic enzymes accumulates in cereals, which impair the structural and mechanical properties of the crumb of pastry products, as a result of which the crumb of the product becomes sticky and wrinkled. The work was aimed at developing a multicomponent mixture to improve the quality of pastry products, the formulation of which includes a mixture of germinated grains. A «Solodok» multicomponent mixture has been developed, which has a positive effect on the organoleptic and structural-mechanical properties of the product crumb. The mixture contains safe food additives and ingredients: ground cinnamon, dry wheat gluten, apple pectin, ascorbic acid. It has been established that the introduction of the «Solodok» multicomponent mixture into the dough leads to the replacement of the fermentation process with the stage of sedimentation. The use of a multicomponent mixture leads to an improvement in the organoleptic characteristics of rich products, an increase in the specific volume of products, and an improvement in the development of the porosity of products. Adding a mixture of sprouted grains and a «Solodok» multicomponent mixture leads to a change in the traditional taste, the products acquire a pleasant aftertaste of sprouted cereals and cinnamon. The use of a mixture of germinated grains and a «Solodok» multicomponent mixture in the recipe for pastry products leads to a decrease in the energy value of pastry products in comparison with the control.
Keywords: pastries; germinated grains; multicomponent mixture; nutritional value; germinated cereals; випічка; зерно пророщене; суміш багатокомпонентна; харчова цінність; пророщені зернові культури; кафедра технології хлібопекарських і кондитерських виробів; кафедра технології молока і молочних продуктів